The Gender Gap and Career Path of the Academic Profession Under the Civil Service System at a Religious University in Jakarta, Indonesia - Toyibah, Dzuriyatun (KOMUNITAS: International Journal of Indonesian Society and Culture, 2018)
In this article I argue that male academics under civil servant system in a religious university still dominate the highest academic positions. This study applies logistic regression (binary and ordinal regression) since the available data, especially for dependent variable, is categorical and it does not fulfil the assumption of ordinary least square. By applying ordinal regression, gender is found to be undetected compared to other variables (age, length of tenure, and educational qualifications). Nevertheless, a statistical analysis utilising binary regression indicates that gender is a significant factor along with length of tenure and educational qualifications. The data obtained from the religious university is made up of the curriculum vitae of 749 academics in 2012 who are nearly all civil servants at the university.